UNVEILING A NEW CURTAIN: THE APPLICABILITY OF CISG ON SALES OF DRONES: - Gracia, Chelsea (Transnational Business Law Journal, 2022)
Drones have become an integral part of the aviation industry, encompassing a wide range of sizes and functions. This paper examines the interpretation and application of the United Nations Convention on Contracts for the International Sale of Goods (CISG) to the sale of drones. While drones are not explicitly excluded from the CISG, their absence from its provisions can be attributed to the CISG's formation predating their widespread commercialization. The absence of specific provisions addressing drone sales within the CISG has led to diverse interpretations. However, considering the CISG's objective of establishing a uniform legal framework and promoting good faith in international trade, extending its application to the sale of drones is conceivable. As an internationally recognized legal instrument for the sale of goods, the CISG provides a convenient framework for parties involved in drone transactions. However, the CISG must also consider the intricacy and risks associated with certain goods, which may conflict with other legal regulations or introduce complexities in their legal treatment. Drones exhibit diverse types, functionalities, and operational contexts, and their regulation varies significantly across different countries due to airspace and national sovereignty considerations.